Great American speeches - Douglas, Melvyn 1901-1981; Price, Vincent 1911-1993; Begley, Ed 1901-1970; Sandburg, Carl 1878-1967 (Caedmon, 1958)
Presents speeches by Patrick Henry, George Washington, Thomas Jefferson, Josiah Quincy, Henry Clay, Charles Sumner, Robert Toombs, Abraham Lincoln, Robert E. Lee, and William Jennings Bryan